A Perempuan Adat, Habitus, dan Ketahanan Pangan: Kajian Pada Masyarakat Hukum Aat Kasepuhan Citorek, Banten: A STUDY CUSTOMARY LAWA COMMUNITY OF KASEPUHAN CITOREK, BANTEN - Surati, Surati (LIPI Press, 2023)
This paper aims to analyze the role of traditional women and their habits in realizing family food security in the Kasepuhan Citorek traditional community, Lebak Regency, Banten Province. This research uses qualitative methods, with an approach to Pierre Bourdieu's theoretical framework regarding the concept of habitus. Data was collected through in-depth interviews, observations, and literature studies. This research shows that the habitus that exists in the Kasepuhan Citorek traditional community influences how traditional women know how to achieve family food security. Indigenous women's knowledge of food is not formed just like that but is formed from everyday life. Indigenous women's efforts to achieve food security cannot be separated from the power relations that occur in the living context of the Kasepuhan Citorek traditional community. This living context consists of various customary rules regarding control over food source land. The habitus of traditional women who obey family and customary rules, on the other hand, weakens access and control over land management and, on the other hand, can strengthen family food security, where food reserves are sufficient.